A Systematic Review and Meta-Analysis of the Clinical Appropriateness of Blood Transfusion in China. Issue 50 (December 2015) - Zhu, Changtai; Gao, Yulu; Li, Zhiqiang; Li, Qinyun; Gao, Zongshuai; Liao, Yanqiu; Deng, Zhifeng
Abstract : Abstract: The issue of the clinical appropriateness of blood transfusion has become a focus of transfusion medicine worldwide. In China, irrational uses of blood have often been reported in recent years. However, to date there lacks a systematic review of the rational uses of blood. This study aimed to determine the clinical appropriateness of blood transfusion in China. We searched PubMed, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database, WanFang Database, and Chinese BioMedical Literature Database, and the retrieval cut-off date was June 31, 2015. SPSS 17.0 and MetaAnalyst 3.13 were employed as the statistics tools in this review. A pooled rate of clinical inappropriateness of transfusion was analyzed by DerSimonian–Laird method. In this study, a total of 39 observational studies were included, which related to 75, 132 cases of blood transfusion. According to the meta-analysis results, the overall incidence of clinical inappropriateness of transfusion in China was estimated to be 37.3% (95% confidence interval [CI] [32.1, 42.8]). The subgroup analyses revealed that the pooled rates of clinical inappropriateness of transfusion of plasma, red blood cells (RBCs), cryoprecipitate, and platelets were 56.3% (95% CI [45.8, 66.2]), 30.9% (95% CI [27.1, 35.0]), 25.2% (95% CI [13.2, 42.7]), and 14.1% (95% CI [8.8, 21.9]), respectively. However, the pooled incidence of inappropriateness of transfusion in operative departments was 47.5% (95% CI [36.8, 58.3]), which was significantly higher than that in nonoperative departments, 25.8% (95% CI [18.7, 34.4], P < 0.05). The overall rates of inappropriate use were 36.7% (95% CI [30.2, 43.6]) in major cities and 37.5% (95% CI [31.2, 44.3]) in other cities, respectively; there was no statistically significant difference ( P > 0.05). In conclusion, China has suffered from a disadvantage in the clinical appropriateness of blood transfusion, especially in plasma and RBC use. In future, comprehensive measures should be implemented in order to improve the clinical appropriateness of blood transfusion. Abstract : Supplemental Digital Content is available in the text